1998
DOI: 10.1002/(sici)1096-9136(199810)15:10<878::aid-dia686>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Beyond retinal screening: digital imaging in the assessment and follow-up of patients with diabetic retinopathy

Abstract: Many screening methods are available for detecting diabetic retinopathy. However, once patients develop retinopathy, it is unclear as to what method should be used for their review. We describe a novel and integrated system for the screening and treatment of diabetic retinopathy using high street optometrists for primary screening and digital imaging as a secondary screening tool, with referral to a joint retinal clinic only where ophthalmological intervention may be required. Of 3586 patients screened by opto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…9 Screening studies have shown that up to 10% of diabetics have sight-threatening retinopathy. 10,11 Up to 40% of type II diabetics have some retinopathy at diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…9 Screening studies have shown that up to 10% of diabetics have sight-threatening retinopathy. 10,11 Up to 40% of type II diabetics have some retinopathy at diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity to detect microaneurysms is not as good on digital photography as on conventional 35-mm photography, although several authors have found good agreement between both techniques for DR grading, [14][15][16] the poorest agreement between DR grades was recorded at level 21, characterized by the presence of few microaneurysms. [17][18][19] This is due to the lower resolution of digital photography, which makes the images granular and increases the number of questionable lesions when grading for microaneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…Our results do not seem to be as good as Kerr's, who found a kappa of 0.90 for the agreement between 35 mm and digital images for the detection of vision-threatening retinopathy [2]. The most likely explanation is that their results were from a DR screening service, with lower rates of vision-threatening DR than in our population.…”
Section: Discussionmentioning
confidence: 99%
“…The resolution of 35-mm images is still higher than the digital images used in ophthalmology. Two British studies report an 85-90% sensitivity for the detection of sight-threatening retinopathy using digital images, which is considered to be sufficient [2,3]. On the other hand, an American survey reports that 15% of neovascularisations are missed on digital photographs.…”
Section: Introductionmentioning
confidence: 99%